Tracing the formation of molecular clouds via [C ii], [C i], and CO emission - Clark, Paul C.; Glover, Simon; Ragan, Sarah E.; Duarte-Cabral, Ana (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. Our understanding of how molecular clouds form in the interstellar medium (ISM) would be greatly helped if we had a reliable observational tracer of
Gesehen am 21.04.2020